(untitled) (Research, Society and Development, 2020)
Objectives: to analyze the risk factors for hypoglycemia in critically ill patients using Continuous Insulin Infusion found in the medical records of patients admitted to an Intensive Care Unit and to describe nurses’ knowledge about the risk factors for hypoglycemia in critically ill patients using ICI. Methodology: Quantitative and qualitative study of the descriptive and exploratory type. The ICU setting of a state public hospital in Rio de Janeiro. The sample included medical records and nurses. Results: risk factors in medical records: delay in hourly glycemia; vasoactive drugs; organic failure; diabetes mellitus, sepsis; hemodialysis; acute or chronic renal failure; zero / oral diet and liver disease. Nurses reported inadequate or absent nutritional support, delays in blood glucose measurements, inadequate adjustments to the insulin protocol and hemodynamic instability are risk factors for hypoglycemia in ICI. Final considerations: Nurses’ knowledge of the risk factors for hypoglycemia during ICI is necessary.